Kinetics of antibody response in BALB/c and C57BL/6 mice bitten by Phlebotomus papatasi. - Michaela Vlkova; Iva Rohousova; Jitka Hostomska; Lucia Pohankova; Lenka Zidkova; Jan Drahota; Jesus G Valenzuela; Petr Volf (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Phlebotomine sand flies are blood-sucking insects transmitting Leishmania parasites. In bitten hosts, sand fly saliva elicits specific immune response and the humoral immunity was shown to reflect the intensity of sand fly exposure. Thus, anti-saliva antibodies were suggested as the potential risk marker of Leishmania transmission. In this study, we examined the long-term kinetics and persistence of anti-Phlebotomus papatasi saliva antibody response in BALB/c and C57BL/6 mice. We also tested the reactivity of mice sera with P. papatasi salivary antigens and with the recombinant proteins. METHODOLOGY/PRINCIPAL FINDINGS: Sera of BALB/c and C57BL/6 mice experimentally bitten by Phlebotomus papatasi were tested by ELISA for the presence of anti-saliva IgE, IgG and its subclasses. We detected a significant increase of specific IgG and IgG1 in both mice strains and IgG2b in BALB/c mice that positively correlated with the number of blood-fed P. papatasi females. Using western blot and mass spectrometry we identified the major P. papatasi antigens as Yellow-related proteins, D7-related proteins, antigen 5-related proteins and SP-15-like proteins. We therefore tested the reactivity of mice sera with four P. papatasi recombinant proteins coding for most of these potential antigens (PpSP44, PpSP42, PpSP30, and PpSP28). Each mouse serum reacted with at least one of the recombinant protein tested, although none of the recombinant proteins were recognized by all sera. CONCLUSIONS: Our data confirmed the concept of using anti-sand fly saliva antibodies as a marker of sand fly exposure in Phlebotomus papatasi-mice model. As screening of specific antibodies is limited by the availability of salivary gland homogenate, utilization of recombinant proteins in such studies would be beneficial. Our present work demonstrates the feasibility of this implementation. A combination of recombinant salivary proteins is recommended for evaluation of intensity of sand fly exposure in endemic areas and for estimation of risk of Leishmania transmission.